Penerapan Teknologi Panel Surya Portabel sebagai Solusi Akses Energi Mandiri bagi Masyarakat Desa Terpencil di Pulau Adonara, Kabupaten Flores Timur, Nusa Tenggara Timur - Angelica Maran; Dominikus Rinto (UNITY: Journal of Community Service, 2026)
Limited access to electricity remains a major challenge for communities in remote areas, including several villages on Adonara Island, East Flores Regency, East Nusa Tenggara. The archipelagic geographical condition has restricted the optimal expansion of conventional electricity networks, causing communities to experience difficulties in fulfilling basic energy needs. This community service program aimed to implement portable solar panel technology as an environmentally friendly, practical, and locally suitable solution for independent energy access. The implementation method included energy needs assessment, renewable energy technology education, installation of portable solar panel systems, user training, maintenance guidance, and evaluation after implementation. The results showed that portable solar panel technology improved community access to alternative energy sources for lighting, communication device charging, and small-scale household productive activities. The program also increased community awareness regarding renewable energy utilization and independent energy management. The implementation of portable solar panels provides a relevant approach to supporting energy independence among remote rural communities and strengthening renewable energy adoption in island regions.